The Elevated Endogenous Reactive Oxygen Species Contribute to the Sensitivity of the Amphotericin B-Resistant Isolate of Aspergillus flavus to Triazoles and Echinocandins - Liang, Tianyu; Chen, Wei; Yang, Xinyu; Wang, Qiqi; Wan, Zhe; Li, Ruoyu; Liu, Wei (Frontiers in Microbiology, 2021)
Aspergillus flavus has been frequently reported as the second cause of invasive aspergillosis (IA), as well as the leading cause in certain tropical countries. Amphotericin B (AMB) is a clinically important therapy option for a range of invasive fungal infections including invasive aspergillosis, and in vitro resistance to AMB was associated with poor outcomes in IA patients treated with AMB. Compared with the AMB-susceptible isolates of A. terreus, the AMB-resistant isolates of A. terreus showed a lower level of AMB-induced endogenous ROS, which was an important cause of AMB resistance. In this study, we obtained one AMB-resistant isolate of A. flavus, with an AMB MIC of 32 μg/mL, which was sensitive to triazoles and echinocandins. This isolate presented elevated endogenous ROS levels, which strongly suggested that no contribution of decreased AMB-induced endogenous ROS for AMB-resistance, opposite to those observed in A. terreus. Further, we confirmed that the elevated endogenous ROS contributed to the sensitivity of the AMB-resistant A. flavus isolate to triazoles and echinocandins. Further investigation is needed to elucidate the causes of elevated endogenous ROS and the resistance mechanism to AMB in A. flavus.